Effects of a xu-argument based iterative continuation task on an EFL learner's linguistic and affective development: Evidence from errors, self-initiated error corrections, and foreign language learning attitude. (June 2021) - Zhang, Sumin; Zhang, Lawrence Jun
Abstract: This longitudinal study investigated the effects of a xu -argument based iterative continuation task (XBICT) on an EFL learner's processing of different English linguistic items, overall EFL achievement (EFLA), and foreign language learning attitude (FLLA). The treatment material was taken from a novel, divided into 19 parts, which the EFL learner was asked to read and then extend. pre-test and post-test scores, frequencies of the different types of errors and self-initiated error corrections (SC), and observations of the learner behaviors were collected as data for analysis. Results show significant correlations among the different errors and self-initiated error corrections, suggesting that EFL learning is an integrated system, where errors in one linguistic item can be strong indicators of errors elsewhere. Results also show significant improvement in the EFL learner's processing of past temporal morphemes, overall EFL achievement, and foreign language learning attitude, despite the fact that self-initiated error corrections of spellings are the most frequent while corrections of articles are the least common. These findings suggest that XBICT could be an effective approach in EFL learning but its efficacy could vary with reference to different linguistic items. Some pedagogical implications are discussed. Highlights: Eeffects of a xu -argument based iterative continuation task were investigated. Task-effects on the learner's overall learning achievement and learning (FLL) attitude were examined. Participant made significant improvement in processing past temporal morphemes, learning achievement, and attitude. Self-initiated corrections of spellings were the most frequent while corrections of articles were the least common. The continuation task was found effective but its efficacy with different linguistic items varied.